2012
DOI: 10.1113/expphysiol.2012.066217
|View full text |Cite
|
Sign up to set email alerts
|

Role of the parasympathetic nervous system in cardioprotection by remote hindlimb ischaemic preconditioning

Abstract: New findings r What is the central question of this study?Ischaemia-reperfusion of peripheral tissues protects the heart from subsequent myocardial ischaemia-reperfusion-induced injury and cardiac dysfunction, a phenomenon referred to as 'remote ischaemic preconditioning' (rIPC). This study addressed whether activation of sensory afferent nerves in the ischaemic hindlimb and vagal efferent nerves innervating the heart mediate rIPC. This investigation was designed to determine the participation of the vagus ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 29 publications
7
107
2
2
Order By: Relevance
“…The activation of the peripheral sensory fibers involves activation of the PKCγ isoform. 439 In some studies, activation of the autonomic nervous system through spinal and supraspinal reflexes [435][436][437]442 was mandatory to reduce IS in the ischemic/reperfused myocardium, 32,92,434,435,437,443 in others it was not. 432,444 Of importance, humoral transfer of protection with plasma or dialysate obtained after the peripheral preconditioning cycles to another individual or individual heart, even across species, is possible and highlights the functional importance of the humoral transfer signal.…”
Section: Cardioprotective Signal Transfer During Ricmentioning
confidence: 99%
“…The activation of the peripheral sensory fibers involves activation of the PKCγ isoform. 439 In some studies, activation of the autonomic nervous system through spinal and supraspinal reflexes [435][436][437]442 was mandatory to reduce IS in the ischemic/reperfused myocardium, 32,92,434,435,437,443 in others it was not. 432,444 Of importance, humoral transfer of protection with plasma or dialysate obtained after the peripheral preconditioning cycles to another individual or individual heart, even across species, is possible and highlights the functional importance of the humoral transfer signal.…”
Section: Cardioprotective Signal Transfer During Ricmentioning
confidence: 99%
“…Also, an additional involvement of neuronal pathways either during the initiation of the RIPC stimulus, its transfer, or the installation of protection in the pig myocardium cannot be excluded. 45 …”
Section: Myocardial Signal Transduction Of Ripcmentioning
confidence: 99%
“…The researchers found that cardioprotective effects of VNS including reduced infarct size and decreased ventricular fibrillation episodes were abolished by muscarinic blockade (38). On the other hand, the protective signal of remote IPC reaches the heart through the vagus nerve and activation of muscarinic receptors (9).…”
Section: Discussionmentioning
confidence: 99%